Elaboración, Control e Implementación de un sistema Ball & Beam - Jiménez Quizhpe, Jefferson Michael (2025)
This research presents the development of a classical PID control system for the Ball & Beam model, aimed at stabilizing the position of a ball on an inclined beam. A low-cost prototype was built, integrating seven 3D-printed components and four electronic devices: an Arduino UNO, a Sharp GP2Y0A21YK0F infrared sensor, an MG995 servo motor, and a power supply. The mathematical model was formulated using the Lagrangian method, and the transfer function was derived with MATLAB and LabVIEW, achieving a 97.28% fit. The PID control was implemented and tuned using LabVIEW, through programming blocks that read sensor data, calculate PID parameters, and control the servo motor. The interface included tools for real-time data plotting and logging measurements to Excel files. The system proved to be stable and efficient during real-world testing, validating the derived transfer function as a reliable tool for designing control strategies. This development integrates mechanical design, mathematical modeling, automatic control, and programming, offering a functional and affordable solution for educational purposes.